The Leadership of al-Azhar Alumni in Managing Religious and Ethnic Conflicts in Malaysia: Kepimpinan Alumni al-Azhar dalam Pengurusan Konflik Keagamaan dan Kaum di Malaysia - Abdullah, Mustaffa; Abdul Mukti, Fakhrudin (Jurnal Usuluddin, 2025)
Malaysia is a country renowned for one of its unique characteristics, a pluralistic society. The long course of history has been a major factor contributing to the existence of various differences among the Malaysian population in many aspects. These differences, which add to the distinctiveness of the nation, require proper management, as the failure to handle them appropriately could lead to worrying conflicts, potentially resulting in hostility and division that may threaten national peace. Accordingly, this writing was conducted to examine the actions taken by selected alumni of al-Azhar University who have served as leaders in addressing conflicts. This article employs qualitative methods, particularly library research, by reviewing previous studies to identify interreligious and interethnic issues and analyzing the actions of selected al-Azhar alumni, with special attention to the approaches they adopted in managing conflicts. The selected alumni include Prof. Emeritus Dato’ Dr. Mahmood Zuhdi Abdul Majid, Dato’ Ustaz Haji Fadzil Mohd Noor, Tan Sri Dato’ Seri Tuan Guru Haji Abdul Hadi Awang, Tan Sri Dr. Abdul Hamid Othman, Tan Sri Dato’ Seri Dr. Abdullah Md Zin, Datuk Seri Dr. Mujahid Yusof Rawa, and Dato' Syeikh Haji Mohd Murtadza Ahmad. The findings indicate that the leadership of the al-Azhar alumni applied diplomatic approaches, engaging in wise and harmonious negotiations among the parties involved and religious approaches, by providing clear and courteous explanations and guidance.